2018
DOI: 10.1016/j.meegid.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis genetic diversity among children of low-income daycare center in Southeastern Brazil

Abstract: Blastocystis, an unicellular anaerobic eukaryote, is known to be a very common intestinal parasite found in humans and animals fecal samples worldwide. Currently, there is an increasing interest to yield insights into its prevalence and diversity in human populations living in poor and deprived areas. In this study, we describe the prevalence and genetic variability of Blastocystis isolates obtained from daycare center attendees aged 0 to 6years and staff, as well as some children family members and their dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
52
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 53 publications
7
52
2
5
Order By: Relevance
“…In some studies, it has been observed that this subtype has been strongly related to rural populations [ 8 , 43 ]. It is possible to hypothesize that the migration phenomenon [ 42 ] occurs mainly from the displacement of these rural communities infected with Blastocystis ST3 haplotype 1 spreading this parasite into the cities.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, it has been observed that this subtype has been strongly related to rural populations [ 8 , 43 ]. It is possible to hypothesize that the migration phenomenon [ 42 ] occurs mainly from the displacement of these rural communities infected with Blastocystis ST3 haplotype 1 spreading this parasite into the cities.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira-Arbex et al [45] Melo et al [49] David et al [9] Branco et al [58] Miné et al [66] Alarcón et al [68] Kobayashi et al [76] Seguí et al [50] Takizawa et al [64] Borges et al [63] Kulik et al [65] Subtotal (I^2 = 95.61%, p = 0.00) Subtotal (I^2 = 99.28%, p = 0.00)…”
Section: Rio De Janeiromentioning
confidence: 99%
“…In developing countries, Blastocystis sp. is, with prevalence up to 100%, a practically obligate finding in some populations (El Safadi et al, 2014 ; Poulsen et al, 2016 ; Mohammad et al, 2017 ; Oliveira-Arbex et al, 2018 ), whereas the prevalence reported in industrialized countries most commonly ranges between 7 and 50% (Bart et al, 2013 ; Scanlan et al, 2014 , 2016 ; El Safadi et al, 2016 ; Seyer et al, 2017 ). While the frequent occurrence of Blastocystis sp.…”
Section: Introductionmentioning
confidence: 99%